Financial Directions and Budget Trends in Government Healthcare - Sachs, Michael; Abdullah, Fareed; Madonko, Thokozile; Jonas, Kim; Slingers, Nevilene; Zvawada, Tanaka; Ewinyu, Arabo; Shedi, Olwethu (Southern Centre for Inequality Studies (SCIS), 2023)
This working paper provides evidence and analysis that can assist in taking forward the agenda of the Presidential Health Compact. It does so by reviewing the financial performance of the government healthcare system over the last decade. After assessing the financial management performance, it looks at the “financial health” challenges facing the system, including the problems of accruals and medico-legal claims. The report then examines the budget pressures faced by provincial healthcare departments, as well as the different allocation of resources and levels of care across provinces. It ends with a conclusion and tentative reflections informed by the evidence.
Keywords: Public Health; Health Financing; National Health Insurance; Presidential Health Compact; Financial Management; Healthcare services; Health Budgets; Medico-legal claims; Primary healthcare; Public Economy